Post-crisis political economy: neoliberalism or Islamic alternative? - Md. , Moniruzzaman (Macrothink Institute, 2014)
The global financial crisis that unfolded since the end of 2006 has shaken the very foundation of the Western free-market economic system. Its fundamental regulatory principle of the separation of state and market is now seriously discredited. The objective of this article is to argue that the economic principles of Islam can provide a better alternative to the free-market system. Firstly, an Islamic economic system is highly integrative where the purpose and interest of the state and the individual citizen overlap and are complimentary to each other. So, market and state are rather inseperable in Islamic political economy. Secondly, the free-market system is fundamentally oriented to the philosophy of unlimited consumption, that is – greatest number produces greatest happiness, which demands production and appropriation of resources beyond needs. But the Islamic economic philosophy puts restrictions on unnecessary consumption, thereby capping competition over resources. These two essential principles in Islamic political economy are highly interdependent on state and individual agency of a human being. Therefore, once the economic needs and purpose of the state and the individual citizen are properly enmeshed, it produces a balanced market system. Islamic political economy has moral regimes and instrumental structure for economic behavior that reinforce each other.